Abrasion and impact resistance of concrete before and after exposure to freezing and thawing cycles. (10th August 2019) - Ismail, Mohamed K.; Hassan, Assem A.A.
Highlights: The abrasion and impact resistance of scaled and non-scaled concrete were studied. Different SCMs, coarse aggregate sizes and volumes were investigated. The pre-exposure to freeze-thaw cycles reduced the abrasion and impact resistance. Abraded surfaces exhibited higher scaling damaged compared to non-abraded ones. MK showed the highest improvement in the durability of concrete. Abstract: This study evaluated the abrasion and impact resistance of a number of self-consolidating and vibrated concretes before and after exposure to freezing and thawing cycles in the presence of de-icing salts (salt scaling). The study investigated the effects of supplementary cementing materials (fly ash (FA), slag (SL), silica fume (SF), and metakaolin (MK)), binder contents (250 kg/m 3 and 500 kg/m 3 ), coarse aggregate size (10 mm and 20 mm), and coarse-to-fine (C/F) aggregate ratio (0.7 and 2). Around 32.5% extra average scaling damage was observed in the specimens that were exposed to abrasion before freezing and thawing compared to non-abraded specimens exposed to freezing and thawing. In addition, the pre-exposure to freezing and thawing cycles significantly reduced the impact and abrasion resistance, especially in concrete with low binder content and concrete with high C/F aggregate ratio. Concretes with SF and/or MK showed the highest resistance to abrasion and impact loading (before and after the exposure to salt scaling) while concrete with FA showed the lowest resistance. The results also indicated that using higher C/F aggregate ratio decreased the resistance of concrete to freezing and thawing and impact loading while no significant effect was observed when the coarse aggregate size was changed.